Mengintegrasikan Nilai-Nilai Etika Sufi dalam Kampanye Etika Lingkungan: Sebuah Studi Kualitatif tentang Generasi Z di Indonesia - Ahmad, Farchan Musthofa; Nadhif, M. Alfin; Mevia, Melani Febrya Arta; Hidayatullah, Ahmad Fauzan (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2024)
This article addresses the primary issue of environmental degradation caused by excessive human consumption and unsustainable development models. The study employs a critical analysis of the New Environmental Paradigm (NEP) by Catton and Dunlap to explore the complex interactions between humans and the natural environment. Methodologically, the research utilizes qualitative data from various sources, including historical texts and contemporary studies, to illustrate how socio-cultural values and practices contribute to environmental crises. Key findings indicate that the overexploitation of natural resources, coupled with inadequate awareness of the intrinsic relationship between humans and nature, exacerbates environmental damage. The research highlights the potential of Generation Z to lead behavioral changes towards more sustainable lifestyles through social media and technological engagement. By integrating Tasawuf (Sufi) ethical values, which emphasize simplicity, ecological balance, and empathy towards all creation, Generation Z can foster a movement towards environmental preservation. The study underscores the importance of re-educating society on ethical environmental practices to mitigate ongoing environmental issues and promote sustainability.